RNA Virus-Encoded miRNAs: Current Insights and Future Challenges - Nanbo, Asuka; Furuyama, Wakako; Lin, Zhen (Frontiers in Microbiology, 2021)
MicroRNAs are small non-coding RNAs that regulate eukaryotic gene expression at the post-transcriptional level and affect a wide range of biological processes. Over the past two decades, numerous virus-encoded miRNAs have been identified. Some of them are crucial for viral replication, whereas others can help immune evasion. Recent sequencing-based bioinformatics methods have helped identify many novel miRNAs, which are encoded by RNA viruses. Unlike the well-characterized DNA virus-encoded miRNAs, the role of RNA virus-encoded miRNAs remains controversial. In this review, we first describe the current knowledge of miRNAs encoded by various RNA viruses, including newly emerging viruses. Next, we discuss how RNA virus-encoded miRNAs might facilitate viral replication, immunoevasion, and persistence in their hosts. Last, we briefly discuss the challenges in the experimental methodologies and potential applications of miRNAs for diagnosis and therapeutics.